Seismic fragility and damage assessment of reinforced concrete bridge pier under long-duration, near-fault, and far-field ground motions. (June 2021) - Todorov, Borislav; Billah, A.H.M. Muntasir
Abstract: Observations from recent earthquakes around the world have revealed the destructive nature of near-fault ground motions that cause significant damage to structures. On the other hand, the effect of long-duration motions on seismic demands has attracted a lot of interest over the last decade. This study aims to numerically explore how long-duration (LD) motions and near-fault (NF) ground motions affect the seismic performance of a seismically designed bridge pier and compare the response with short duration far-field (FF) motions. A fiber based nonlinear finite element model of a bridge pier is used for evaluating the damage potential of different types of ground motions. The bridge is assumed to be a major route bridge located in Western Canada and is designed following the performance-based seismic design requirements of the Canadian Highway Bridge Design Code. A set of 20 long-duration motions, 20 spectrally equivalent near-fault and far-field motions are used to study the effect of ground motions on drift and damage measures of the bridge pier. The results indicate that since the current design guidelines consider neither the ground motion duration effect nor the pulse effect of near-fault motions, damage measures for performance-based design should be reviewed to take into account the duration effect as well as the velocity pulse associated with NF motions.